Influence of temperature on Saccharomyces cerevisiae UE-ME3 response to titanium dioxide nanoparticles - Capela-Pires, J (2011)
Titanium dioxide is a polymorphic material which can be found in nature in three mineral phases: rutile, anatase and brookite, the most unstable and of less interest. The form of NP-rutile TiO2 (<100 nm) is described as one of the most toxic compound. While living organisms have been exposed with nanoparticles from millions of years ago and may be adapted to low levels of these materials, the increase of industrial capacity of synthesis, manipulation and massive use in electronic, energy and catalysis processes has increase the environmental levels of nanomaterials in several regions of the planet. The nanotoxicology is an emerging field for research, since fixed mass, density and surface reactivity are features of nanoparticles that contribute for the generation of ROS. The main intention of this work was to determine the influence of temperature and titanium dioxide nanoparticles on the growth of S. cerevisiae UE-ME3, a wine wild-type strain of Alentejo, Portugal.